The Impact of Tax Disputes on Tax Collection in Algeria A Case Study of the Directorate of Taxes of the Wilaya of Bordj Bou Arreridj (2021–2024) - djaiz, Karim (Journal of Research in Finance and Accounting, 2025)
This study aims to delve into the issue of tax disputes, which holds great significance in the field of taxation due to the complexity of tax laws and the specific nature of their procedures, which distinguish them from other types of administrative disputes. This has motivated us to undertake this research, which seeks to clarify and explain in detail the concept of tax disputes, their underlying causes, and the procedures they entail, in order to highlight their impact on the tax collection process-one of the most important sources of revenue upon which the state relies to finance the public treasury. Ultimately, the study aims to enhance tax revenues and ensure the coverage of public expenditures, thereby contributing to economic development and growth across various sectors.